Assessed Deforestation and Its Environmental Impacts: Padre Abad Province - Meza Arquiñigo, Carlos (2011)
The study is aimed at assessing the problems of deforestation through the application of Geographic Information System, which is impacting the environment, for the purpose of showing the critical areas for better spatial and resource management, in this regard we set ourselves the following objectives: To study and analyze the deforestation and environmental change in order to interpret the resulting environmental impacts, Province of Padre Abad, in order to recommend measures to be taken for the management, environmental management are evolving as deforested areas. The automation of graphic information and graphs, as well as the formation of the database we involve the use of GIS functions to identify problems occurring in the landscape.